Multi-Tap Mobile Phone Text Entry : Key-Press Operators For Keystroke Level Model - Srour, Ayman I. H. (2008)
The Keystroke Level Model (KLM) has been utilized to predict the user behaviors and activities with desktop system. Recently, the mobile device application designers could use updated KLM model to predict the consumed time while users use mobile devices, but when designers use this method to evaluate the text entry they still face some difficulties with the calculation of long equations, due to multi-tap technology. This study proposes new KLM operators to facilitate the time calculation process for text entry using traditional mobile keypad. Updated KLM operators are used to predict the user behavior in interacting with mobile devices in general and text entry in specific. The expected results contribute in estimating the consumed time accurately.